2022
DOI: 10.2478/eko-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Water Quality of Akwa Ibom State North-West District, Nigeria, using Water Quality Indices and Palmer Pollution Index

Abstract: Freshwater bodies of Akwa Ibom State North-West District, Nigeria, were studied between May and December 2021 at seven sampling stations based on human activities. The indices used were water quality index (WQI) for drinking water purpose, comprehensive pollution index (CPI) for aquatic life sustainability, and Palmer pollution index (PPI) for organic pollution. Thirteen physicochemical parameters were scrutinized using standard methods and compared with the World Health Organization (WHO) standards. All the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Based on the foregoing, the buckets used in fetching water from these wells could also serve as a source of planktonic introduction. The presence of some taxonomic groups only and/or in high numbers in wells 4 and 5; suggests enrichment from the environment (Khalil et al, 2021;Jonah and Archibong, 2022). The community structure showed that number of taxa ranged between 8 (well 2) and 13 (wells 4 and 5) and the number of individuals ranged between 120 individuals (well 2) and 157 individuals (well 5).…”
Section: -Plankton Composition Abundance and Distributionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the foregoing, the buckets used in fetching water from these wells could also serve as a source of planktonic introduction. The presence of some taxonomic groups only and/or in high numbers in wells 4 and 5; suggests enrichment from the environment (Khalil et al, 2021;Jonah and Archibong, 2022). The community structure showed that number of taxa ranged between 8 (well 2) and 13 (wells 4 and 5) and the number of individuals ranged between 120 individuals (well 2) and 157 individuals (well 5).…”
Section: -Plankton Composition Abundance and Distributionmentioning
confidence: 97%
“…The composition, abundance and distribution of plankton can be used to reliably assess the water quality of aquatic bodies and no single particular physicochemical parameter is responsible for the fluctuations of plankton populations (Anyanwu and Mbekee, 2020;Jonah et al, 2020;Anyanwu et al, 2021a, b;Jonah and Archibong, 2022). The mean and range of the physicochemical parameters are summarized in Table 1.…”
Section: -Physicochemical Parametersmentioning
confidence: 99%
“…The maximum value recorded at the peak of the rainy season (September 2022) suggests the largest volume of water via runoff into the water accompanied by solids particles. The elevated values in June 2022 for pH, nitrate and phosphate were ascribed to the seasonal influence (Anyanwu et al 2022a;Jonah & Archibong, 2022) while the higher concentrations of magnesium, calcium and sodium in dry month (January 2023) are ascribed to many factors such as reduction of volume water, reduced rainfall, high temperature and evaporation (Ling et al, 2017b). Calcium ion is one of the major inorganic substances present in nearly all water systems attributable to its easy solubility from all rocks, including limestone, chalk, dolomite and gypsum (Bartram & Ballance, 1996).…”
Section: Relationship Between Environmental Variables and The Insects...mentioning
confidence: 99%